Cardiovascular effects of space radiation: implications for future human deep space exploration. (November 2019) - Mitchell, Adam; Pimenta, Dominic; Gill, Jaspal; Ahmad, Haris; Bogle, Richard
Background: A manned mission to Mars has been contemplated by the world's largest space agencies for a number of years. The duration of the trip would necessitate a much longer exposure to deep space radiation than any human has ever been exposed to in the past. Concern regarding cancer risk has thus far stalled the progress of deep space exploration; however, the effect of space radiation on the cardiovascular system is significantly less well understood. Discussion: Damage by radiation in space is mediated by a number of sources, including X-rays, protons and heavier charged atomic nuclei (HZE ions, the high-energy component of galactic cosmic rays). Previously, only lunar mission astronauts have been exposed to significant deep space radiation, with all other missions being low earth orbits only. The effect of this radiation on the human body has been inconclusively studied, and the long-term damage caused to the vascular endothelium by this radiation due to the effect of high-energy particles is not well known. Conclusion: Current radiation shielding technology, which would be viable for use in spacecraft, would not eliminate radiation risk. Similar to how a variety of shielding techniques are used every day by radiographers, again without full risk elimination, we need to explore and better understand the effect of deep space radiation in order to ensure the safety of those on future space missions.